ASPEK SOSIAL DAN NILAI PENDIDIKAN DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - IRMA, CINTYA NURIKA; Asri, Tisatun (Universitas Hamzanwadi, 2021)
The research aims to determine and describe the existence of a matematics teacher in the novel Guru Aini, socio-cultural background and educational values contained in the novel. The research is a descriptive research method qualitative content analysis. The research novel Guru Aini is examined with the approach of sociology literature. Validation is used triangulation theory with stages of reading, records, and analysis of the document. The result of this research incate that the existence of a mathematics teacher most feared by students. This is because mathematics is considered a difficult subject to understand so that many students who dislike mathematics. Then the socio-cultural background in Guru Aini’s novel includes customs and beliefs such as the habit of sprinkling sand into the air while avoiding danger, the language used in Indonesian wit a combination of Sumatera language, the religion that many Islamic figures adhere to, the work that is being carried out namely teachers and others, and the character’s last education is D-3 and high school. Finnaly, the educational value contained in Guru Aini’s novel includes the value of social education which is depicted from interaction of the character with community, the value of moral education which is depicted from attitudes and behavior of the characters, the value of religious education which is depicted from the teachings of Islam in the novel and the educational value of strunggle from character efforts in achieving his dreams. Keywords: Sociology, Literature, Novel, Value of Education